가동형 삽입물을 사용한 후방십자인대 절제형 슬관절 전치환술의 단기 추시 결과 - 문영완; Young Wan Moon; 도관홍; Gwan Hong Do; 한정훈; Jeong Hoon Han; 이도경; Do Kyeong Lee; 서재곤; Jai Gon Seo (Knee Surgery and Related Research, 23(2), 2011)
목적: 최근 후방십자인대를 절제한 후 포스트가 없는 가동형 경골 삽입물을 적용시켰을 때 관절의 안정성을 지킬 수 있는 고도 적합성(ultra-congruence)의 관절면을 가진 경골 삽입물이 고안되어 슬관절 전치환술에 적용되고 있으나 이에 대한 문헌보고는 거의 없다. 본 연구는 이러한 삽입물을 이용한 수술의 임상적 및 방사선학적 결과를 네비게이션을 이용하여 분석하고자 하였다. 대상 및 방법: 2006년 9월부터 2008년 12월까지 네비게이션을 이용한 슬관절 전치환술을 시행받은 환자들 중 후방십자인대를 절제한 후 가동형 경골 삽입물을 적용한 70명의 95예를 대상으로 하였다. 추적관찰 기간은 최소 24개월로 평균 40개월이었으며, Knee Society Score system을 통해 슬관절 점수와 기능점수를 수술 전과 최종 추시 시점에 각각 측정하여 임상적 평가를 하였고, 임상적 결과에 영향을 줄수 있는 관절선의 높이 변화에 대하여 네비게이션에 기록된 측정값을 토대로 5 mm 기준으로 A군(≤5mm)과 B군(＞5 mm)으로 나누어 비교, 평가하였다. 수술 전과 최종 추시 시점의 단순 방사선 사진상하지의 기계적 축의 각, 슬개골의 경사각 등을 측정하고, 방사선학적 평가를 하였다. 결과: 추시 기간 24 개월 이상(평균 40개월)의 대상자 70명(95예)이 추적 관찰 가능하였다. 임상적 결과로 KSS의 평균 슬관절 점수는 수술 전 43.4점에서 최종 추시 시점 90.6점으로(p＜0.0001), 평균 기능점수는 수술 전 51점에서 최종 추시 시점 88.4점으로(p＜0.0001) 호전되었다. 임상결과에 영향을 줄 수 있는 관절선의 높이 변화는 -1-12 mm로 평균 5.82 mm이었으며, 이에 대하여 5 mm를 기준으로 두 개의 군으로 나누어 임상적 및 방사선학적 평가를 비교하였으나 통계적 차이를 나타내지 않았다. 하지의 기계적 축의 각은 수술 전 평균 내반 10.01˚ 에서 최종 추시 시점 평균 내반 1.89˚ 로 향상되었고, 통계적으로 유의하였다(p＜0.0001). 슬개골의 경사각은 수술 전과 최종 추시 시점에서 평균 8.8˚와 9.3˚로 각각 측정 되었고, 이는 통계적 차이를 나타내지 못하였다(p=0.89). 결론: 네비게이션을 이용하여 후방십자인대를 절제한 후 가동형 경골 삽입물을 적용한 슬관절 전치환술의 최소 2년 추시 관찰 결과 임상적 및 방사선학적으로 양호한 결과를 보여주었다. Purpose: Recently, a mobile ultracongruent polyethylene insert was used to increase joint stability in the posterior cruciate ligament sacrificed total knee arthroplasty with non-posted mobile bearing. However, as yet there have been no reports about this implant. In this study, the clinical and radiological results of surgery using the implant were analyzed through a navigation system. Materials and Methods: The subjects included 95 cases of 70 patients to whom the rotating tibial implant was applied after posterior cruciate ligament resection among the patients who underwent total knee arthroplasty from September 2006 to December 2008. The follow-up duration was at least 24 months, and 40 months on average. For clinical evaluation, the knee score and functional scores were measured preoperatively and at the time of final follow-up. With reference to a 5 mm joint line change measurement recorded by the navigation system, which can affect the clinical result, the comparison and evaluation were performed by dividing the subjects into group I (≤5 mm) and group II (＞5 mm). Radiological evaluation was performed by measuring the angle of the mechanical axis of the lower extremities and the patella tilting angle preoperatively and at the time of final follow-up using plain radiographs. Results: Seventy subjects (95 cases) were followed up for at least 24 months. According to the clinical results, the mean KSS knee score improved from a preoperative score of 43.4 to a final follow-up score of 90.6 (p＜0.0001). In addition, the mean functional score improved from a preoperative score of 51 to a final follow-up score of 88.4 (p＜0.0001). Finally, the mean joint line change, which can affect the clinical result, was 5.82 mm, ranging from -1 to 12 mm. The clinical and radiological evaluations were performed by dividing the subjects into two groups in relation to the reference value of 5 mm, but no significant difference was found. The mechanical axis angles of the lower extremities improved from the preoperative value of varus 10.01˚ to the final follow-up value of varus 1.89˚, and the difference was significant (p＜0.0001). The mean patella tilting angles were 8.8˚ and 9.3˚, respectively, at the time before the operation and after the final follow-up; this difference was not significant (p=0.89). Conclusion: Good clinical and radiological results were observed after at least two years of follow-up subsequent to total knee arthroplasty, in which a rotating ultracongruent polyethylene insert was applied after posterior cruciate ligament resection using a navigation system.